You have a GP where 2nd term is 4 -----> ar=4
the fifth term is four times the third term ---- ar^4 = ar^2
ar^4 = ar^2
divide by ar^2, r can't be zero
r^2 = 1
r = ± 1
then in ar=4
if r = +1, a = 4
if r = -1, a = -4
Do C and D by simply using the formulas that you learned.
A geometric sequence , the fifth term is four times the third terms, the second term is 4.
If r<0, determine:
A) the value of r, the common ratio.
B) the value of a.
C) the tenth term.
D) the sum of the 15 terms.
3 answers
In geometric sequence:
an = a1 ∙ r ⁿ ⁻ ¹
a2 = a1 ∙ r
a3 = a1 ∙ r ²
a5 = a1 ∙ r ⁴
The fifth term is four times the third terms mean; a5 = 4 ∙ a3
a1 ∙ r ⁴ = 4 ∙ a1 ∙ r ²
Divide both sides by ( a1 ∙ r ² )
r ² = 4
r = ± √4
r = ± 2
In this case r < 0 so:
r = - 2
The second term is 4 mean; a2 = 4
a1 ∙ r = 4
a1 ∙ ( - 2 ) = 4
Divide both sides by - 2
a1 = 4 / - 2
a1 = - 2
a10 = a1 ∙ r⁹
a10 = ( - 2 ) ∙ ( - 2 )⁹
a10 = ( - 2 ) ∙ ( - 512 )
a10 = 1024
Sn = a1 ( 1 − r ⁿ ) / ( 1 − r )
In this case n = 10
S10 = ( - 2 ) ∙ [ 1 − ( - 2 )¹⁰ ) / [ 1 − ( - 2 ) ]
S10 = ( - 2 ) ∙ ( 1 − 1024 ) / ( 1 + 2 )
S10 = ( - 2 ) ∙ ( − 1023 ) / 3
S10 = 2046 / 3
S10 = 682
an = a1 ∙ r ⁿ ⁻ ¹
a2 = a1 ∙ r
a3 = a1 ∙ r ²
a5 = a1 ∙ r ⁴
The fifth term is four times the third terms mean; a5 = 4 ∙ a3
a1 ∙ r ⁴ = 4 ∙ a1 ∙ r ²
Divide both sides by ( a1 ∙ r ² )
r ² = 4
r = ± √4
r = ± 2
In this case r < 0 so:
r = - 2
The second term is 4 mean; a2 = 4
a1 ∙ r = 4
a1 ∙ ( - 2 ) = 4
Divide both sides by - 2
a1 = 4 / - 2
a1 = - 2
a10 = a1 ∙ r⁹
a10 = ( - 2 ) ∙ ( - 2 )⁹
a10 = ( - 2 ) ∙ ( - 512 )
a10 = 1024
Sn = a1 ( 1 − r ⁿ ) / ( 1 − r )
In this case n = 10
S10 = ( - 2 ) ∙ [ 1 − ( - 2 )¹⁰ ) / [ 1 − ( - 2 ) ]
S10 = ( - 2 ) ∙ ( 1 − 1024 ) / ( 1 + 2 )
S10 = ( - 2 ) ∙ ( − 1023 ) / 3
S10 = 2046 / 3
S10 = 682
The sum of the 15 terms.
Sn = a1 ( 1 − r ⁿ ) / ( 1 − r )
where n = 15
S15 = ( - 2 ) ∙ [ 1 − ( - 2 )¹⁵ ] / [ 1 − ( - 2 ) ]
S15 = ( - 2 ) ∙ [ 1 − ( - 32 768 ) ] / ( 1 + 2 )
S15 = ( - 2 ) ∙ ( 1 + 32 768 ) / 3
S15 = ( - 2 ) ∙ 32 769 / 3
S15 = - 65 538 / 3
S15 = - 21 846
Sn = a1 ( 1 − r ⁿ ) / ( 1 − r )
where n = 15
S15 = ( - 2 ) ∙ [ 1 − ( - 2 )¹⁵ ] / [ 1 − ( - 2 ) ]
S15 = ( - 2 ) ∙ [ 1 − ( - 32 768 ) ] / ( 1 + 2 )
S15 = ( - 2 ) ∙ ( 1 + 32 768 ) / 3
S15 = ( - 2 ) ∙ 32 769 / 3
S15 = - 65 538 / 3
S15 = - 21 846